國小家庭作業類型的預測與中介效果：從教學風格到任務價值 Predicting and Mediating the Effects of Elementary School Homework Type: From Teaching Style to Task Value - 李宜玫 Yi-Mei Lee; 陳姵穎 Pei-Ying Chen (National Taiwan Normal University, 2010)
本研究旨在分析教師的任務價值是否為教學風格與家庭作業指派類型之間的中介變項。以臺北縣、市區域與學校規模進行分層便利取樣，共得有效教師問卷301 份（男76、女225）。分別以學生中心教學風格為自變項，家庭作業內容與操作方式指派的頻率為結果變項，教師的任務價值為中介變項。透過階層多元迴歸分析教師教學風格的預測力與任務價值的中介效果。結果顯示：一、效用價值對知識能力展現作業具部分中介效果；二、興趣及代價對人格教育養成作業則為完全中介；三、效用價值及代價對靜態操作業有部分中介效果；四、興趣、效用價值及代價對動態操作業有部分中介效果，惟效用價值為負向關聯。由此可見，教師指派不同類型家庭作業時，除了學生中心教學風格的影響，對應不同的任務價值具有完全或部分的中介效果。由於任務價值是教師對於家庭作業的功能與教學目標的理念與認知評估，未來若要促成國小家庭作業的多元性與豐富化，凸顯生活經驗與帶得走的能力，並考量學生負荷與家庭資源等各種複雜的相關因素，就需要透過更多教師同儕之間的教學理念對話、交流與家庭作業形式觀摩等方式，以增進教師對家庭作業指派的效能。 The purpose of this study was to understand the homework type assigned by elementary teachers by analyzing there three task values that were mediators between teaching style and homework type. A total of 301 valid questionnaires, 76 males and 225 females, were received. Scales used in this study were "Teaching Style Scale", "Homework Task Value Scale", and "Homework Inventory Survey" to gather independent, mediation and dependent variables. Hierarchical regression analysis proved that the mediation function about task value. The results of this study indicated that: (1) Utility value was partly mediated between teaching style and knowledge & competence homework. (2) Interest value and cost were mediated between teaching style and character-education homework. (3) Utility value and cost were partly mediated between teaching style and statically operational homework. (4) Interest, utility value, and cost were partly mediated between teaching style and dynamically operational homework. But utility value had a negative relationship. Therefore, when teachers designed different styles of homework, they had different task valued. In the future, if we should enrich and diversify the homework, emphasize student life and competence, and consider parental contribution, we could increase the chance of dialogue, enhance communication, and increase imitation among teacher peers.